A prospective quality improvement study in the emergency department targeting paediatric sepsis. Issue 10 (31st March 2016) - Long, Elliot; Babl, Franz E; Angley, Eleanor; Duke, Trevor
Abstract : Objective: Quality improvement sepsis initiatives in the paediatric emergency department have been associated with improved processes, but an unclear effect on patient outcome. We aimed to evaluate and improve emergency department sepsis processes and track subsequent changes in patient outcome. Study design: A prospective observational cohort study in the emergency department of The Royal Children's Hospital, Melbourne. Participants were children aged 0–18 years of age meeting predefined criteria for the diagnosis of sepsis. The following shortcomings in management were identified and targeted in a sepsis intervention: administration of antibiotics and blood sampling for a venous gas at the time of intravenous cannulation, and rapid administration of all fluid resuscitation therapy. The primary outcome measure was hospital length of stay. Results: 102 patients were enrolled pre-intervention, 113 post-intervention. Median time from intravenous cannula insertion to antibiotic administration decreased from 55 min (IQR 27–90 min) pre-intervention to 19 min (IQR 10–32 min) post-intervention (p≤0.01). Venous blood gas at time of first intravenous cannula insertion was performed in 60% of patients pre-intervention vs 79% post-intervention (p≤0.01). Fluids were administered using manual push-pull or pressure-bag methods in 31% of patients pre-intervention and 84% of patients post-intervention (p≤0.01). Median hospital length of stay decreased from 96 h (IQR 64–198 h) pre-intervention to 80 h (IQR 53–167 h) post-intervention (p=0.02). This effect persisted when corrected for unequally distributed confounders between pre-intervention and post-intervention groups (uncorrected HR: 1.36, 95% CI 1.04 to 1.80, p=0.02; corrected HR: 1.34, 95% CI 1.01 to 1.80, p=0.04). Conclusions: Use of quality improvement methodologies to improve the management of paediatric sepsis in the emergency department was associated with a reduction in hospital length of stay.